Provable Security : 13th International Conference, ProvSec 2019, Cairns, QLD, Australia, October 1–4, 2019, Proceedings /: 13th International Conference, ProvSec 2019, Cairns, QLD, Australia, October 1–4, 2019, Proceedings. (2019) - Unknown
No abstract available